From Impetus to Engagement: Ecological Perspectives on Content Faculty Agency in CLIL Collaborations at a Canadian University - Wallace, Amanda (Comparative and International Education / Éducation comparée et internationale, 2025)
⁠⁠⁠⁠⁠⁠⁠This qualitative case study explores the experiences of content faculty (CF) participating in interdisciplinary collaborations for Content and Language Integrated Learning (CLIL) in Canadian higher education. Using an ecological lens, this study examines the motivations, enactments, and contextual factors shaping agency across three disciplinary cases. Data from semi-structured interviews reveal that collaborative dynamics and the enactment of agency are shaped by disciplinary expertise, interpersonal relationships, and the interplay of personal histories, future aspirations, institutional structures, and professional contexts within the ecologies of these partnerships. They underscore the importance of recognizing faculty contributions and addressing institutional barriers to strengthen collaborative efforts. In addition to extending CLIL research beyond predominantly European and Asian contexts, the findings offer insights into how institutions can better support the language and literacy development of their multilingual students.